Fabrication and Characterization of Formamide-Modified Magnesium Aluminum Layered Double Hydroxide as Reinforcing Nanofiller for Thermoplastic Starch Film - Murat, Semiha; Akyol, Emel; Eroglu, Mehmet S. (TAYLOR & FRANCIS INC, 2025)
Thermoplastic starch (TPS) is produced by processing starch at high temperatures with plasticizers like water or glycerol, transforming it into an amorphous polymer. A major issue with natural polymers is their high water permeability and tendency to swell, which weakens mechanical properties and limits direct use. Combining starch with clay in nanocomposites offers significant potential for new engineering materials. This study investigates enhancing TPS properties with formamide-modified magnesium-aluminum layered double hydroxide (MgAl LDH) nanofillers. MgAl LDH (Mg/Al molar ratio 3:1) was synthesized via co-precipitation, modified with formamide (MgAl-F LDH), and dispersed in the TPS matrix using twin-screw extrusion. Characterization techniques, including tensile testing, water contact angle, FTIR, XRD, SEM, TEM, and TGA/DTG, comprehensively examined the properties of both the fillers and the resulting nanocomposite films. The findings indicated that the modified MgAl-F LDH nanoparticles exhibited an average size of approximately 48 nm, with lower crystallinity compared to unmodified MgAl LDH (average size similar to 50 nm). The incorporation of MgAl-F LDH significantly enhanced the thermal stability and hydrophobicity of the TPS films, although a reduction in tensile strength was observed. These results suggest that formamide modification of MgAl LDH can optimize TPS composites, expanding their potential applications in packaging and biodegradable materials. [GRAPHICS] .
Keywords: Biopolymer; formamide; magnesium-aluminum layered double hydroxide (MgAl LDH); nanocomposite; thermoplastic starch (TPS); MECHANICAL-PROPERTIES; DELAMINATION; PLASTICIZERS; NANOSHEETS; WATER; Polymer Science